Réponses

2014-08-19T16:43:02+02:00
Horizontalement
1)
x + 6 = 500
x = 500 - 6
x = 494

3x - 2 = x + 8
3x - x = 8 + 2
2x = 10
x = 10/2
x = 5

2)
2x = 54
x = 54/2
x = 27

x + 5 = 2x - 8
x - 2x = - 5 - 8
- x = - 13
x = 13

3)
x - 62 = 750
x = 750 + 62
x = 812

4)
3x - 12450 = 235278
3x = 235278 + 12450
3x = 247728
x = 247728/3
x = 82576

5)
8 = 5 + x
8 - 5 = x
3 = x
x = 3

3x - 8 = 849,5
   2
3x - 8 = 849,5 x 2
3x - 8 = 1699
3x = 1699 + 8
3x = 170
x = 170/3
x = 569

Verticalement

1)
2 - 3 (x + 1) = -x - 85
2 - 3x - 3 = -x - 85
- 3x + x = - 85 + 3 - 2
- 2x = - 84
x = 84/2
x = 42

x - 83 = 0
x = 83

2)
2x - 150 = 3x - 9932
2x - 3x = - 9932 + 150
- x = - 9782
x = 9782

3)
- 7x = - 28
7x = 28
x = 28/7
x = 4

- 3x = - 465
x = 465/3
x = 155

4)
1000 - x =- 276
- x = - 276 - 1000
x = 1276

5)
x + x + x + 5 = 4x - 48
3x + 5 = 4x - 48
3x - 4x = - 48 - 5
x = 53

70 = x + 1
70 - 1 = x
x = 69


4 9 4 ∞ 5
2 7 ∞ 1 3
∞ 8 1 2 ∞
8 2 5 7 6
3 ∞ 5 6 9